Agaricus brasiliensis KA21 May Prevent Diet-Induced Nash Through Its Antioxidant, Anti-Inflammatory, and Anti-Fibrotic Activities in the Liver - Nakamura, Anna (Foods, 2019)
Non-alcoholic steatohepatitis (NASH) is a progressive disease that occurs in the liver. As the number of people with NASH has increased, effective prevention and treatment strategies are needed. Agaricus brasiliensis KA21 (AGA) is a mushroom native to Brazil and is considered a healthy food because of its purported health benefits, including its antioxidant properties. In this study, we focused on the oxidative stress that accompanies the onset of NASH and examined whether AGA can prevent NASH development through its antioxidant activity. We used a mouse model of NASH in which pathogenesis was promoted by dietary induction. Supplementation with AGA attenuated the development of hepatic fibrosis, which is a characteristic feature of late-stage NASH. This effect appeared to be mechanistically linked to an AGA-promoted reduction in hepatic oxidative stress. These results demonstrate a novel role for AGA in NASH prevention.